Uncertain accommodation: aboriginal identity and group rights in the Supreme Court of Canada - Panagos, Dimitrios (UBC Press, 2016)
"In 1982, Canada formally recognized Aboriginal rights within its Constitution. The move reflected a consensus that states should and could use group rights to protect and accommodate subnational groups within their borders. Decades later, however, no one is happy. This state of affairs, Panagos argues, is rooted in a failure to define what aboriginality means, which has led to the promotion and protection of a single vision of aboriginality–that of the justices of the Supreme Court. He concludes that there can be no justice so long as the state continues to safeguard a set of values and interests defined by non-Aboriginal people."– Provided by publisher.